The earliest evidence of wheeled vehicles in Europe and the Near East - Bakker, Jan Albert
The appearance of wheeled vehicles in Europe and the Near East during the 4th millennium BC is a major socio-economic development. In the past, eminent archaeologists such as Childe (1951), Piggott (1979; 1983) and, more recently, Sherratt (1981; 1997) have argued for diffusion of wheeled vehicles from the Near East to Europe. In contrast, other archaeologists as e.g. Hausler (1992) and Vosteen (1996) stressed the local development of wheeled vehicles in Europe. The question of diffusion versus independent development is an old issue in archaeology. Judging by the archaeological data in the 1990s, it seems that wheeled vehicles developed more or less simultaneously or diffused very fast from Mesopotamia to Europe. We favour the latter possibility. It is difficult to explain how this technological transmission occurred in the 4th millennium BC, but Europe and the Near East were never isolated from each other during this period. First we will